2015
DOI: 10.21608/asnj.2015.59822
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Cognitive Functions Among Elderly Patients Attending Out Patient Clinics in Assiut University Hospital

Abstract: Cognitive impairment is common among older adults. It doesn't not only threaten their quality of life but also has a negative impact on caregivers, as well as represents challenges in different clinical care settings. The aim of the study assess cognitive functions and identify the prevalence of cognitive impairment among elderly patients attending outpatient clinics in Assiut University Hospital. Material and Methods: the study included 580 elderly patients recruited from outpatient clinics of Assiut Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Growth regulators play a major role in the success of plant tissue culture. It was found that the balance between auxins and cytokinins plays a major role in the emergence and multiplication of vegetative shoots of the plant, as it requires adding them in specific concentrations depending on the genetic composition of the plant, the type of plant part, its internal content of hormones and the stage of growth (9). Furthermore, cytokinins have a role in plant cell division, differentiation, and axillary bud growth (10).…”
Section: Introductionmentioning
confidence: 99%
“…Growth regulators play a major role in the success of plant tissue culture. It was found that the balance between auxins and cytokinins plays a major role in the emergence and multiplication of vegetative shoots of the plant, as it requires adding them in specific concentrations depending on the genetic composition of the plant, the type of plant part, its internal content of hormones and the stage of growth (9). Furthermore, cytokinins have a role in plant cell division, differentiation, and axillary bud growth (10).…”
Section: Introductionmentioning
confidence: 99%